The Role Of The Ppkn Teacher In Improving Student Discipline At Muhammadyah Private SD 2 Binjai Timur - Ismail Ismail; Arsip Perangi-Angin; Seget Tartiyoso; Sri Kurnia Hastuti Sebayang; Dewi Rulia Sitepu (Eduvest - Journal of Universal Studies, 2021)
The role of the PKN teacher is that with the motivation and directions given by the Civics teacher, student discipline can be formed from the example of the teacher and also from each one so that students are more disciplined in class and at school. Discipline is a form of obedient behavior and is subject to applicable regulations, but compliance is more emphasized on self-awareness not because of coercion. The school discipline applied to the students of Muhammadiyah 2 Binjai Timur Private Elementary School is quite good so that the discipline applied at school becomes positive. This research was conducted by means of observation and interviews with the principal of SD Swasta Muhammadyah 2 Binjai Timur with homeroom teachers and several students.